Characterization of a papain-like cysteine protease essential for the survival of Babesia ovis merozoites - Carletti, Tamara; Mesplet, Maria; Mira, Anabela; Weir, William; Shiels, Brian; Gonzalez Oliva, Abel; Schnittger, Leonhard; Florin-Christensen, Mónica; Barreto, Carmo (2017)
Babesia ovis, a tick-transmitted intraerythrocytic protozoan parasite, causes severe infections in small ruminants from Southern Europe, Middle East, and Northern Africa. With the aim of finding potential targets for the development of control methods against this parasite, sequence analysis of its genome led to the identification of four putative cysteine proteases of the C1A family. Orthology between B. ovis, B. bovis, T. annulata, and T. parva sequences showed that each B. ovis C1A peptidase sequence clustered within one of the four ortholog groups previously reported for these piroplasmids. The ortholog of bovipain-2 of B. bovis and falcipain-2 of Plasmodium falciparum, respectively, was designated “ovipain-2” and further characterized. In silico analysis showed that ovipain-2 has the typical topology of papain-like cysteine peptidases and a highly similar predicted three dimensional structure to bovipain-2 and falcipain-2, suggesting susceptibility to similar inhibitors. Immunoblotting using antibodies raised against a recombinant form of ovipain-2 (r-ovipain-2) demonstrated expression of ovipain-2 in in vitro cultured B. ovis merozoites. By immunofluorescence, these antibodies reacted with merozoites and stained the cytoplasm of infected erythrocytes. This suggests that ovipain-2 is secreted by the parasite and could be involved in intra- and extracellular digestion of hemoglobin and/or cleavage of erythrocyte proteins facilitating parasite egress. A significant reduction in the percentage of parasitized erythrocytes was obtained upon incubation of B. ovis in vitro cultures with anti-r-ovipain-2 antibodies, indicating an important functional role for ovipain-2 in the intra erythrocytic development cycle of this parasite. Finally, studies of the reactivity of sera from B. ovis-positive and negative sheep against r-ovipain-2 showed that this protease is expressed in vivo, and can be recognized by host antibodies. The results of this study suggest that ovipain-2 constitutes a potential target for immunotherapies and drug development against ovine babesiosis.